The Influence of Digital Marketing, Brand Awareness, and Word of Mouth on Purchase Decisions: Pengaruh Digital Marketing, Brand Awareness, dan Word of Mouth Terhadap Keputusan Pembelian - Andrianti, Berlina; Oetardjo, Mas (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of Digital Marketing, Brand Awareness, and Word Of Mouth on Purchase Decisions. This study uses a quantitative approach. Sampling in the study used accidental sampling technique, with the number of respondents as many as 95 respondents from Bund's Pizza consumers. Data collection techniques using questionnaires distributed through questionnaires. The data analysis technique in this study used multiple linear regression analysis. Data processing in this study used the software program SPSS 22 (Statistical Program For the Social Sciences). The results show that: Digital Marketing affects the Purchase Decision on Bund's Pizza Products, Brand Awareness affects the Purchase Decision on Bund's Pizza Products, and Word Of Mouth affects the Purchase Decision on Bund's Pizza Products.